Validity and Practicality of Guided Discovery based E-Module in Facilitating Student Mathematical Creative Thinking Ability at Junior High School - Anisha Wulandari; Irma Fitri; Erdawati Nurdin; Annisa Wahidatul Asmi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research aimed to develop a guided discovery-based e-module to facilitate students' mathematical creative thinking abilities at Junior High School/ Islamic Junior High School. It was Research and Development with the ADDIE model, consisting of 5 development steps: analysis, design, development, implementation, and evaluation. The subjects of this research were 22 eighth-grade students at the Private Junior High School of YPPI Perawang. Validity and practicality questionnaires were used to collect data. Validity data were collected from expert validators, and practicality data were collected through questionnaires distributed to students. The research findings showed that the validity score was 90% (very valid) and the practicality score was 86% (convenient). Based on the findings, the Guided Discovery-based e-module was found to be valid and practical in facilitating students' mathematical creative thinking at Junior High School/ Islamic Junior High School.